The Effect of Servant Leadership and Work Culture on Account Officer Performance With Reward as A Moderating Variable (A Study At PT Permodalan Nasional Madani Mekaar Yogyakarta Branch) - Trihanung Wulandriyo; Siti Safaria (Winter Journal: IMWI Student Research Journal, 2026)
Variations in the performance of Account Officers (AOs) at PT Permodalan Nasional Madani (PNM) Mekaar Yogyakarta Branch, as reflected in differences in lending distribution across operational areas, indicate challenges in human resource management. This condition highlights the need for organizations to not only focus on achieving performance targets but also to strengthen leadership practices and organizational work culture to ensure sustainability. This study aims to empirically examine the effect of servant leadership and work culture on the performance of Account Officers (AOs), as well as to analyze the moderating role of the reward system in these relationships. This research employs a quantitative approach with a correlational research design. Primary data were collected through a structured survey using closed-ended questionnaires with a five-point Likert scale, distributed to active Account Officers at PT PNM Mekaar Yogyakarta Branch. Respondents were selected using a purposive sampling technique based on predefined criteria. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3 Professional software to test the relationships between variables simultaneously and to identify moderating effects. The findings of this study are the better the work culture, the better the performance; the better the servant leadership, the better the performance; the better the rewards, the better the performance; moderation of rewards strengthens the relationship between servant leadership and performance; moderation of rewards strengthens the relationship between work culture and performance.